Paleometry as a key tool to deal with paleobiological and astrobiological issues: some contributions and reflections on the Brazilian fossil record - Gomes, Amanda L. S.; Becker-Kerber, Bruno; Oses, Gabriel L.; Prado, Gustavo; Becker Kerber, Pedro; De Barros, Gabriel E. B.; Galante, Douglas; Rangel, Elidiane [UNESP]; Bidola, Pidassa; Herzen, Julia; Pfeiffer, Franz; Rizzutto, Marcia A.; et al. (Cambridge Univ Press, 2019)
Investigations into the existence of life in other parts of the cosmos find strong parallels with studies of the origin and evolution of life on our own planet. In this way, astrobiology and paleobiology are married by their common interest in disentangling the interconnections between life and the surrounding environment. In this way, a cross-point of both sciences is paleometry, which involves a myriad of imaging and geochemical techniques, usually non-destructive, applied to the investigation of the fossil record. In the last decades, paleometry has benefited from an unprecedented technological improvement, thus solving old questions and raising new ones. This advance has been paralleled by conceptual approaches and discoveries fuelled by technological evolution in astrobiological research. In this context, we present some new data and review recent advances on the employment of paleometry to investigations on paleobiology and astrobiology in Brazil in areas such biosignatures in Ediacaran microbial mats, biogenicity tests on enigmatic Ediacaran structures, research on Ediacaran metazoan biomineralization, fossil preservation in Cretaceous insects and fish, and finally the experimental study on the decay of fish to test the effect of distinct types of sediment on soft-tissue preservation, as well as the effects of early diagenesis on fish bone preservation.
Keywords: Biogenicity; biomineralization; biosignatures; Ediacaran; fossilization process; microbial mats